Modified telephone - Fam, J.C (University Malaysia Sarawak (UNIMAS), 2001)
This report presents a modify telephone consisting of extra features such as recording of conversation, displaying the number called, on-off LED indicator and external earphone and microphone which controlled by an external switch.